Altered Brain Mitochondrial Metabolism in Healthy Aging as Assessed by in vivo Magnetic Resonance Spectroscopy - Boumezbeur, Fawzi; Mason, Graeme F; de Graaf, Robin A; Behar, Kevin L; Cline, Gary W; Shulman, Gerald I; Rothman, Douglas L; Petersen, Kitt F (Journal of cerebral blood flow and metabolism, 2010)
A decline in brain function is a characteristic feature of healthy aging; however, little is known about the biologic basis of this phenomenon. To determine whether there are alterations in brain mitochondrial metabolism associated with healthy aging, we combined 13C/1H magnetic resonance spectroscopy with infusions of [1-13C]glucose and [2-13C]acetate to quantitatively characterize rates of neuronal and astroglial tricarboxylic acid cycles, as well as neuroglial glutamate–glutamine cycling, in healthy elderly and young volunteers. Compared with young subjects, neuronal mitochondrial metabolism and glutamate–glutamine cycle flux was ∼30% lower in elderly subjects. The reduction in individual subjects correlated strongly with reductions in N-acetylaspartate and glutamate concentrations consistent with chronic reductions in brain mitochondrial function. In elderly subjects infused with [2-13C]acetate labeling of glutamine, C4 and C3 differed from that of the young subjects, indicating age-related changes in glial mitochondrial metabolism. Taken together, these studies show that healthy aging is associated with reduced neuronal mitochondrial metabolism and altered glial mitochondrial metabolism, which may in part be responsible for declines in brain function.